Efek Ukuran Partikel terhadap Disolusi Ibuprofen - Yosephine, Samuella; Intan, Nur; Anjani, Sabrina; Rahma, Shesa; Pudyastuti, Beti; Wijaya, Triyadi Hendra; Kurniawan, Dhadhang Wahyu (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2022)
The dissolution rate is an important characteristic to consider when designing a pharmaceutical dosage form, particularly for oral medications. Ibuprofen is an oral medication with a low dissolution rate. The common solution to this problem is to increase the dose to improve drug absorption and effectiveness in order to achieve therapeutic concentration. Some methods to increase dissolution rates have been explored, such as salt formation, prodrug formation, particle size reduction, crystal modification, micellar solubilization, complex formation, solid dispersion, and self-emulsifying. This review focuses on a strategy for increasing ibuprofen dissolution rate by reducing the particle size of the drug. Reduced particle size could improve ibuprofen solubility, allowing it to be absorbed more easily and achieve the desired therapeutic effect.